524. An Objective Measure of The Host Response Suggests Social Determinants, Rather than Pathobiology, as a Factor in Disparate Sepsis Outcomes Among Races. (15th December 2022) - O'Neal, Hollis R; Sheybani, Roya; Mitchell, Miranda; Tse, Henry T; Shah, Ajay M; Thomas, Christopher B
Abstract: Background: Sepsis is a common and costly condition encountered in United States hospitals and Emergency Departments (ED). Studies have shown that the incidence of sepsis and risk of sepsis morbidity and mortality increases with age. With increased efforts on early detection and process of care, in-hospital sepsis deaths have declined; however, racial disparities have been observed in sepsis-related outcomes. The objective of this study was to assess demographic, severity, and outcome differences among septic patients presenting to the ED self-reporting as White vs. Black, and evaluate the potential of an investigational cellular host response test in risk stratifying these subpopulations for risk of poor outcomes. Methods: The IntelliSep test is an investigational in-vitro diagnostic that quantifies the state of immune activation by measuring the biophysical properties of leukocytes from a routine whole blood sample in under 10 minutes. The result is the IntelliSep Index (ISI), ranging between 0.1-10.0, stratified into three discrete interpretation bands of increasing disease severity risk: Green, Yellow, and Red. Adult patients presenting to the ED with signs or suspicion of infection were prospectively enrolled in four discrete but similar cohorts at multiple sites in the USA (Feb. 2016 – Apr. 2020). All patients had ISI performed and were followed by retrospective chart review for outcome information and sepsis adjudication. Treating clinicians did not have access to assay results, and only those determined to be septic were included in the final analysis. Results: Of the 150 patients included in the analysis, 92 (61%) were White and 58 (39%) Black. No significant differences were observed in biological sex or severity of illness (Fig). Black subjects were significantly younger (mean difference 8.9 years; p < 0.001) compared to Whites. Independent of race, the ISI correlated with increasing likelihood of adverse sepsis-related outcomes. Biological sex and APACHE II scores by ISI Interpretation Band for White and Black Study subjects. Conclusion: The ISI is an objective tool for the quantification of immune activation, and adequately risk-stratifies patients with sepsis for adverse outcomes, independent of race. This finding suggests that social determinants of health, rather than differences in immunobiology, contribute to racial disparities observed in sepsis-related outcomes. Disclosures: Roya Sheybani, PhD, Cytovale: Employee|Cytovale: Stocks/Bonds Henry T. Tse, PhD, Cytovale: Stocks/Bonds Ajay M. Shah, PhD, Cytovale Inc: Board Member|Cytovale Inc: Ownership Interest|Cytovale Inc: Stocks/Bonds.